2012
DOI: 10.1364/oe.20.028544
|View full text |Cite
|
Sign up to set email alerts
|

Efficient second-harmonic generation of a broadband radiation by control of the temperature distribution along a nonlinear crystal

Abstract: We demonstrate an efficient technique for the second harmonic generation (SHG) of the broadband radiation based on the temperature gradient along a nonlinear crystal. The characteristics of Type I non-critical phase-matched SHG of broadband radiation in the LiB(3)O(5) (LBO) crystal with the temperature gradient imposed along the crystal were investigated both numerically and experimentally. The frequency doubling efficiency of the broadband pulsed fiber laser radiation as high as 68% has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…These simple closed-form expressions could be very useful for a practical design of SHG devices. Because of the relative insensitivity of the final conversion efficiency on the system parameters, e.g., the fundamental frequency, it is expected that by choosing the design parameters appropriately, new types of highly efficient frequency converters with large bandwidths could be fabricated with potential applications in short pulses upconversion as shown in [4][5][6][7][8]. An estimation for the required values of the design parameters associated with autoresonant SHG devices is provided in Appendix A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These simple closed-form expressions could be very useful for a practical design of SHG devices. Because of the relative insensitivity of the final conversion efficiency on the system parameters, e.g., the fundamental frequency, it is expected that by choosing the design parameters appropriately, new types of highly efficient frequency converters with large bandwidths could be fabricated with potential applications in short pulses upconversion as shown in [4][5][6][7][8]. An estimation for the required values of the design parameters associated with autoresonant SHG devices is provided in Appendix A.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneering studies of nonlinear optics at the beginning of the 1960s [2,3], SHG was studied extensively in various types of materials and configurations and has been exploited in numerous applications. Over the years, various theoretical and experimental studies have shown that in many systems, the SHG conversion efficiency and bandwidth could be increased by varying the properties of the medium along the direction of the waves propagation [4][5][6][7][8]. Similar conclusions were obtained in other parametric processes, e.g., two-step third-harmonic generation [9], three-wave mixing (TWM) in the undepleted pump regime [10][11][12], and also TWM and four-wave mixing (FWM) where pump-depletion was taken into account [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising approaches is to implement a temperature gradient along the direction of light propagation [36]. This has been experimentally shown in a nonlinear lithium triborate (LiB 3 O 5 -LBO) crystal and has led to improved conversion efficiency in second harmonic generation over a narrow bandwidth [37]. This technique has also been applied to broaden the phase-matching bandwidth in a periodically-poled channel waveguide up to 13 nm [38], as well as to shift the gain wavelength position in a fiber OPA [39].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a 15% improvements in the generated SHG efficiency. At nearly the same time, Regelskis et al [18] employed an alternative oven configuration to provide a temperature gradient along a LiB 3 O 5 (LBO) crystal to achieve 68% of frequency doubling efficiency. The utilized LBO crystal which was embraced by two Brass plates located on the top and bottom of the crystal.…”
Section: Introductionmentioning
confidence: 99%